วาทวิเคราะห์บทละครของหลวงวิจิตรวาทการกับการสร้างค่านิยม - พรพรหม ทิพยมนตรี (จุฬาลงกรณ์มหาวิทยาลัย, 2000)
This thesis aimed at studying Luang Wichit Wadakam s plays in creating values in the period of Marshal Phibolsongkram. The researcher had specified 5 objectives for the thesis : first, to study about the context that was the most important for invention of plays, second, to learn about the themes and main values proposed in Luang Wichit’s plays, third, to learn about the way of inculcating values through plays in the period of Marcha! Phibolsongkram, fourth 1 to investigate communication strategies to transmit these values ; and fifth, to answer the question "What was the best way to persuade people and make them receive these values?." The researcher investigated the structure of the plays using contextual and textual analysis, documentary research and in-depth interview. The results showed that the contextual factors most effecting the invention of Luang Wichit’s plays were politics and public administration. Luang Wichit s most popular plays had as their major theme the inculcating of patriotism and nationalism. Successful plays transmitted these values primarily through sentimental expressions followed by the messages designed by the sender. In some piays, entertainment and logical reasoning were major strategies in transferring messages through episodes in front of the curtain, dialogues, plots, characters and music. The audience was most impressed by music and could remember best the songs used in the plays.